Effects of phosphorus fertilizer rate and Pseudomonas fluorescens strain on field pea (Pisum sativum subsp. arvense (L.) Asch.) growth and yield - Bahram SALEHI; Hashem AMINPANAH (Acta Agriculturae Slovenica)
A field experiment was conducted at Rezvanshahr, Guilan province, Iran, to evaluate the effects of phosphorus fertilizer rate and Pseudomonas fluorescens strains on growth and yield of field pea (Pisum sativum L.). The experimental design was a randomized complete block in a factorial arrangement with three replicates. Factors were phosphorus fertilizer rates (0, 25, 50, 75, and 100 kg P2O5 ha-1 as triple superphosphate), and seed inoculation with P. florescens strains [control (non-inoculated), inoculated with strain R41, and strain R187). Analysis of variance showed that plant height, seed yield, pod number per m2, 100-seed weight, biological yield, harvest index, and leaf P concentration were significantly influenced by phosphorus fertilizer rate and P. florescens strain. At the same time, phosphorus fertilizer rate × P. fluorescens strain interaction was significant only for 100-seed weight. On the other hand, seed number per pod was significantly affected neither by phosphorus fertilizer rate nor by pseudomonas strains. Result showed that seed yield was significantly increased from 1099 ± 67 to 1898 ± 118 kg ha-1 as P2O5 application rate increased from 0 to 75 kg ha-1, and thereafter relatively remained constant. There was no significant difference in seed yield between plants raised from inoculated seeds with P. fluorescens, strain R187 (1664 ± 97 kg ha-1) and those raised from inoculated seeds with P. fluorescens, strain R41 (1669 ± 104 kg ha-1). At the same time, plants raised from inoculated seeds with P. fluorescens (both strains) produced greater grain yield compared to those raised from uninoculated seeds (1370 ± 80 kg ha-1). Based on the results of this study, P2O5 application at the rate of 75 kg ha-1 and inoculation with pseudomonas bacteria are recommended for obtaining the greatest seed yield in field pea.